Not your usual neurodegenerative disease: a case report of neuronal intranuclear inclusion disease with unconventional imaging patterns - Xu, Luyao; Zhang, Hongxia; Yuan, Hanye; Xie, Liwen; Zhang, Junliang; Liang, Zhigang (Frontiers in Neuroscience, 2023)
Background: Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative illness with characteristic brain magnetic resonance imaging (MRI) manifestations: diffuse symmetric white-matter hyperintensities in lateral cerebral ventricle areas in fluid-attenuated inversion recovery (FLAIR) and high-intensity signals along the corticomedullary junction of the frontal-parietal-temporal lobes in diffusion weighted imaging (DWI). Here, we report a case of adult-onset NIID who was misdiagnosed with Susac syndrome (SS) due to unusual corpus callosum imaging findings.Case presentation: A 39-year-old man presented with chronic headache, blurred vision, tinnitus, and numbness in the hands as initial symptoms, accompanied by cognitive slowing and decreased memory. Brain MRI revealed round hypointense lesions on T1-weighted imaging (T1WI) and hyperintense lesions on T2WI/ FLAIR/ DWI in the genu and splenium of the corpus callosum. An initial diagnosis of SS was made based on the presence of the SS-typical symptoms and SS-characteristic radiology changes. Furthermore, the patient's symptoms improved upon completion of a combined pharmacotherapy plan. However, no significant changes were evident 18 months after the brain MRI scan. Eventually, the patient was then diagnosed with NIID based on a skin biopsy and detection of expanded GGC (guanine, guanine, cytosine) repeats in the NOTCH2NLC gene.The present NIID case in which there was simultaneous onset of altered nervous and visual system functioning and atypical imaging findings, the atypical imaging findings may reflect an initial change of NIID leukoencephalopathy.